Analysis of large deformation of deep water drilling riser considering vortex-induced vibration. (April 2023) - Mao, Liangjie; Wu, Maoxia; Zhang, Wenbin; Guo, Changming; Zeng, Song
Abstract: In this study, a dynamic model for large deformation of deepwater drilling riser considering vortex-induced vibration (VIV) and actual ocean load was established. Nonlinear Van der Pol equation was used to simulate the VIV. The model was discretized by finite element method and solved by Newmark-β method. The dynamic characteristics of the riser under different marine environments and working conditions were analyzed. Results show that the force on the flow direction of the riser adds the pulsating drag term, which increases the riser deformation, after VIV is considered. The riser deflection and bending moment increase with the rise in surface velocity, decrease with the increment in top tension, and slightly change with the increase in wind speed and drilling fluid displacement. The rise in surface wind speed will increase the vibration mode and frequency of riser flow direction, while the increment in top tension will decrease the vibration mode and keep the vibration frequency unchanged. Wind speed and drilling fluid displacement slightly influence the riser deflection.